2017
DOI: 10.1021/jacs.7b08161
|View full text |Cite
|
Sign up to set email alerts
|

Achieving One-Electron Oxidation of a Mononuclear Nonheme Iron(V)-Imido Complex

Abstract: A mononuclear nonheme iron(V)-imido complex bearing a tetraamido macrocyclic ligand (TAML), [FeV(NTs)(TAML)]− (1), was oxidized by one-electron oxidants, affording formation of an iron(V)-imido TAML cation radical species, [FeV(NTs)(TAML+•)] (2); 2 is a diamagnetic (S = 0) complex, resulting from the antiferromagnetic coupling of the low-spin iron(V) ion (S = 1/2) with the one-electron oxidized ligand (TAML+•). 2 is a competent oxidant in C–H bond functionalization and nitrene transfer reaction, showing that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 39 publications
3
61
0
Order By: Relevance
“…Notably, although valence tautomerisation is observed in some synthetic porphyrinoid counterparts, 11 , 12 , 14 anion-dependent valence tautomerisation in non-heme iron systems is very uncommon. 40 , 41 The reported radical-cations often show enhanced substrate C–H activation behavior, 47 similar to reports on cytochrome P450, and recently on Mn IV (O-LA)(TBP8Cz˙ + ) (LA = Lewis acid, TBP8Cz = octakis( p-tert -butylphenyl)corrolazinato 3– ) as well. 14 However, we show that radical-cations on sterically unprotected ligands, such as, 1-TAML˙ + , can undergo unprecedented C–H activation followed by nucleophilic halogen substitution on the TAML aryl ring.…”
Section: Resultssupporting
confidence: 74%
“…Notably, although valence tautomerisation is observed in some synthetic porphyrinoid counterparts, 11 , 12 , 14 anion-dependent valence tautomerisation in non-heme iron systems is very uncommon. 40 , 41 The reported radical-cations often show enhanced substrate C–H activation behavior, 47 similar to reports on cytochrome P450, and recently on Mn IV (O-LA)(TBP8Cz˙ + ) (LA = Lewis acid, TBP8Cz = octakis( p-tert -butylphenyl)corrolazinato 3– ) as well. 14 However, we show that radical-cations on sterically unprotected ligands, such as, 1-TAML˙ + , can undergo unprecedented C–H activation followed by nucleophilic halogen substitution on the TAML aryl ring.…”
Section: Resultssupporting
confidence: 74%
“…[35] Especially xanthenei sacommonly used substrate to investigate reaction kinetics of such reactions. [28][29][30][31]33] In the courseo fo ur investigations,w ei nitially reasoned in a similar manner.H owever,m uch to our surprise, we observed that sulfonamides are able to react with xantheneand thioxanthene in the presence of ab enzoquinoned erivativea sas acrificial oxidant and base, without the need for a( transitionmetal) catalyst. Even more interestingly, we also observed that dihydroheteroanthracenes react with commonly used iminoiodanes to afford the corresponding aminationp roduct in the absence of any catalyst (Figure 1).…”
Section: Introductionmentioning
confidence: 79%
“…Therefore, dihydroheteroanthracenes are often assumed to be suitable model substrates to test for basic C−H amination activity, even for relatively non‐reactive nitrene intermediates . Especially xanthene is a commonly used substrate to investigate reaction kinetics of such reactions …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, we reported an iron(V)–imido TAML cation radical complex, [Fe V (NTs)(TAML +. )], which was synthesized by oxidizing an iron(V)–imido complex, [Fe V (NTs)(TAML)], with one‐electron oxidants, such as [Fe III (bpy) 3 ] 3+ , tris(4‐bromophenyl)‐ammoniumyl hexachloroantimonate {[(4‐BrC 6 H 4 ) 3 N ]SbCl 6 }, and [Ru III (bpy) 3 ] 3+ . Herein, we have demonstrated that the oxidation of [Fe V (NTs)(TAML)] occurs on the TAML ligand, not on the iron ion .…”
Section: Methodsmentioning
confidence: 99%